Una riscrittura tempestosa: da Emily Brontë a Beppe Fenoglio passando per Wyler (Mantichora. Italian Journal of Performance Studies, 2020)
La Voce Nella Tempesta, Bebbe Fenoglio’s theatrical rewrite, puts itself in the center of a cultural crossroads because it uses different literary kinds and several communication languages. It unmistakably indicates its “hypotext” in the novel Wuthering Heights by Emily Brontë. In addition, it also delineates its own identity in the elaborate contamination that the author/performer realizes between the narrative adapted text and the homonymous film directed by Wyler. The analysis of the pièce is outside of the exclusive use of analytic categories that are only inherent in the literary kind. Therefore, it puts itself into a tight dialogism of artistic languages that becomes a tool for the writer to transfer a conversational plurality into his work. The pièce is characterized in a performative way because of this relationship. The purpose of this essay is to revalue the creative ingenuity of this theatrical text by analyzing it in a more heterogeneous and multi-perspective vision of tout court. It blends and readdresses the primary observations of immediate and sectorial analysis about Beppe Fenoglio’s brief dramatic artwork.